The impact of surface treatment in 3-dimensional printed implants for early osseointegration: a comparison study of three different surfaces - Jungwon Lee (Nature Portfolio, 2021)
Abstract 3D printing technology has been gradually applied to various areas. In the present study, 3D-printed implants were fabricated with direct metal laser sintering technique for a dental single root with titanium. The 3D implants were allocated into following groups: not treated (3D-None), sandblasted with a large grit and acid-etched (3D-SLA), and target-ion-induced plasma-sputtered surface (3D-TIPS). Two holes were drilled in each tibia of rabbit, and the three groups of implants were randomly placed with a mallet. Rabbits were sacrificed at two, four, and twelve weeks after the surgery. Histologic and histomorphometric analyses were performed for the evaluation of mineralized bone-to-implant contact (mBIC), osteoid-to-implant contact (OIC), total bone-to-implant contact (tBIC), mineralized bone area fraction occupancy (mBAFO), osteoid area fraction occupancy (OAFO), and total bone area fraction occupancy (tBAFO) in the inner and outer areas of lattice structure. At two weeks, 3D-TIPS showed significantly higher inner and outer tBIC and inner tBAFO compared with other groups. At four weeks, 3D-TIPS showed significantly higher outer OIC than 3D-SLA, but there were no significant differences in other variables. At twelve weeks, there were no significant differences. The surface treatment with TIPS in 3D-printed implants could enhance the osseointegration process in the rabbit tibia model, meaning that earlier osseointegration could be achieved.